Glucose- and insulin-induced phosphorylation of the insulin receptor and its primary substrates IRS-1 and IRS-2 in rat pancreatic islets - Velloso, L. A.; Carneiro, E. M.; Crepaldi, S. C.; Boschero, A. C.; Saad, MJA (Elsevier B.V., 1995)
The presence of tyrosine-phosphorylated proteins was studied in cultured rat pancreatic islets, Immunoblotting performed with total extracts of islets cultured in the presence of 1.8 or 5.6 mM glucose revealed at least three distinct tyrosine-phosphorylated bands (25 kDa, 95 kDa and 165-185 kDa). After 12 h incubation in medium containing 1.8 mM glucose, a pulse exposition to 11 or 22 mM glucose or to 10(-7) M insulin led to a substantial increase in the phosphorylation of all three bands, with no appearance of novel bands. Immunoprecipitation with specific antibodies demonstrated that the signal detected at 95 kDa corresponds to the beta subunit of the insulin receptor (IR) while the band at 165-185 kDa corresponds to the early substrates of the insulin receptor, IRS-1 and IRS-2. Immunoprecipitation with IRS-I or IRS-2 antisera detected their association with the lipid metabolizing enzyme phosphatidylinositol 3-kinase (PI 3-kinase), Thus, this is the first demonstration that elements involved in the insulin-signalling pathway of traditional target tissues are also present in pancreatic islets and are potentially involved in auto- and paracrine-signalling in this organ.
Keywords: insulin; insulin receptor; insulin receptor substrate 112; islet of Langerhans